UNIDIRECTIONAL FLOW TRAVELING WAVE PHENOMENON USING NONLINEAR SCHRöDINGER EQUATION - Fathya Putri Alamsyah, Alliya
This final project is learning about unidirectional flow phenomenon in traveling waves using the Nonlinear Schrödinger equation. This project will use numerical approach using Fast Fourier Transform and Order-4 Runge Kutta. In this case, a traveling wave simulation will be carried out based on the Nonlinear Schrödinger equation with certain conditions. Traveling waves will be simulated with some potential or not, then it will be simulated by changing the parameters that we used such as speed and distance between potentials. Then we want to see the effect of changing the parameters used on the phenomenon of unidirectional flow in traveling waves.